A facile graphene oxide based sensor for electrochemical detection of neonicotinoids - Urbanová, Veronika; Bakandritsos, Aristides; Jakubec, Petr; Szambó, Tamás; Zbořil, Radek (Biosensors & bioelectronics, 2017)
The increasing use of neonicotinoids in systematic seed treatment to crops is a serious cause of pollution of water resources and environment. Consequently, food sources can get eventually contaminated. To this end, it is desirable to develop suitable and effective platforms in order to obtain low-cost and sensitive sensors for neonicotinoids detection. In this work, graphene oxide modified electrodes were used as highly efficient electrochemical sensors for detection of two common insecticides - thiamethoxam and imidacloprid. The proposed sensor responded linearly in the concentration range of 10-200µmolL-1 for both analytes and the detection limits were determined as low as 8.3µmolL-1 and 7.9µmolL-1 for thiamethoxam and imidacloprid, respectively. Analytical performance was also evaluated on spiked water and honey samples.
Keywords: thiamethoxam; monitorování životního prostředí; oxidy; biosenzitivní techniky; Imidacloprid; Oxides; Voltammetry; grafit; Environmental Monitoring; oxaziny; Insecticides; Limit of Detection; limita detekce; Biosensing Techniques; řeky; Rivers; chemické látky znečišťující vodu; Graphite; Oxazines; analýza potravin; kontaminace potravin; med; Thiamethoxam; Thiazoles; Imidazoles; Water Pollutants, Chemical; elektrochemické techniky; neonikotinoidy; thiazoly; Food Contamination; Neonicotinoids; imidazoly; Food Analysis; Electrochemical Techniques; Honey; insekticidy; elektrody; Graphene oxide; Nitro Compounds; dusíkaté sloučeniny; Electrodes